Association between conversion to in-center nocturnal hemodialysis and right ventricular remodeling. Issue 6 (3rd August 2017) - Karur, Gauri R; Wald, Ron; Goldstein, Marc B; Wald, Rachel; Jimenez-Juan, Laura; Kiaii, Mercedeh; Leipsic, Jonathon; Kirpalani, Anish; Bello, Olugbenga; Barthur, Ashita; Ng, Ming-Yen; Deva, Djeven P; et al.
ABSTRACT: Background: In-center nocturnal hemodialysis (INHD) is associated with favorable left ventricular (LV) remodeling. Although right ventricular (RV) structure and function carry prognostic significance, the impact of dialysis intensification on RV is unknown. Our objectives were to evaluate changes in RV mass index (MI), end-diastolic volume index (EDVI), end-systolic volume index (ESVI) and ejection fraction (EF) after conversion to INHD and their relationship with LV remodeling. Methods: Of 67 conventional hemodialysis (CHD, 4 h/session, three times/week) patients, 30 continued on CHD and 37 converted to INHD (7–8 h/session, three times/week). Cardiac magnetic resonance imaging was performed at baseline and 1 year using a standardized protocol; an experienced and blinded reader performed RV measurements. Results: At 1 year there were significant reductions in RVMI {−2.1 g/m 2 [95% confidence interval (CI) −3.8 to − 0.4], P = 0.017}, RVEDVI [−9.5 mL/m 2 (95% CI − 16.3 to − 2.6), P = 0.008] and RVESVI [−6.2 mL/m 2 (95% CI − 10.9 to − 1.6), P = 0.011] in the INHD group; no significant changes were observed in the CHD group. Between-group comparisons showed significantly greater reduction of RVESVI [−7.9 mL/m 2 (95% CI − 14.9 to − 0.9), P = 0.03] in the INHD group, a nonsignificant trend toward greater reduction in RVEDVI and no significant difference in RVMI and RVEF changes. There was significant correlation between LV and RV in terms of changes in mass index (MI) ( r  = 0.46), EDVI ( r  = 0.73), ESVI ( r  = 0.7) and EF ( r  = 0.38) over 1 year (all P < 0.01). Conclusions: Conversion to INHD was associated with a significant reduction of RVESVI. Temporal changes in RV mass, volume and function paralleled those of LV. Our findings support the need for larger, longer-term studies to confirm favorable RV remodeling and determine its impact on clinical outcomes.